The Influence of Leadership Style and Competence on Employee Performance Through Discipline As an Intervening Variable in the Environmental and Forestry Service of North Sumatera Province - Herti Aprinawati Giawa; Mahyudin Situmeang; Barham Siregar (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
This study aims to analyze the influence of leadership style and competence on employee performance through discipline at the Environment and Forestry Service of North Sumatra Province. The study used a quantitative approach with a descriptive research type. Data were collected through questionnaires, observations, interviews, and documentation. The study population was 628 employees with a sample of 86 respondents determined using the Slovin formula with a simple random sampling technique. Data analysis was carried out using partial tests (t), simultaneous tests (F), and the coefficient of determination (R²). The results showed that leadership style had a significant effect on employee performance by 51.9% and competence by 63.8% with a significance of 0.000 <0.05. Simultaneously, leadership style and competence had an effect on employee performance by 71.8%, and on discipline by 69.9%. Together, leadership style, competence, and discipline had a significant effect on employee performance by 94.8%. These results indicate that discipline plays a mediating variable in improving employee performance. The better the leadership style and employee competency, the higher the level of employee discipline and performance at the North Sumatra Provincial Environment and Forestry Service. Keywords: Competence, Discipline, Employee Performance, Leadership Style.